IMPACT OF GST LAW WITH REFERENCE TO ECOMMERCE INDUSTRY IN INDIA - Keshri, Kunal (International Tax Law Review, 2023)
Article 366(12A) defines the Goods and Services Tax (GST) as any tax on the supply of goods, services, or both, except taxes on the delivery of alcoholic drinks for human use. In the new Article 366(26A), the word “service” means something other than “products.” Article 366(12) states that all materials, things, and articles are considered to be products. The government considers the GST to be more of a tax reform than a change to the current Indian tax system. They are evaluating all the pros and cons of the indirect taxation system. India was one of 123 countries in the world that used the Value Added Tax (VAT) system. Finance minister P. Chidambaram created plans for VAT and presented them to the Centre and the States on January 17, 2005. VAT replaced the Central Excise Tax at the national level and the Sales Tax System at the state level, which made a significant change to the tax collection process. In 2014, it was proposed that the GST be implemented in India starting from June 2016. The GST is implemented in a “double” way, with one part handled by the Centre (CGST) and another by the State (SGST). The tax base is almost the same for both the federal government and the states. On July 1, 2017, the GST was implemented in India, with three main models: (i) Central GST, (ii) State GST, and (iii) Dual GST. The E-commerce industry in India has been contributing more and more to the Indian economy. To make the most out of a mature and profitable E-commerce industry, retail E-commerce businesses need a stable indirect tax plan to address tax assessment issues they have been facing.